2005
DOI: 10.1021/ja0502324
|View full text |Cite
|
Sign up to set email alerts
|

Three-Dimensional Low Symmetry Mesoporous Silica Structures Templated from Tetra-Headgroup Rigid Bolaform Quaternary Ammonium Surfactant

Abstract: Two kinds of highly ordered mesoporous silica materials (FDU-11, FDU-13) with novel three-dimensional (3-D) tetragonal and orthorhombic structures were synthesized by using tetra-headgroup rigid bolaform quaternary ammonium surfactant [(CH(3))(3)NCH(2)CH(2)CH(2)N(CH(3))(2)CH(2)(CH(2))(11)OC(6)H(4)C(6)H(4)O(CH(2))(11)CH(2)N(CH(3))(2)CH(2)CH(2)CH(2)N(CH(3))(3).4Br] (C(3-12-12)(-)(3)) as a template under alkaline conditions. High-resolution transmission electron microscopy (HRTEM), small-angle X-ray scattering (S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
45
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 77 publications
(47 citation statements)
references
References 77 publications
2
45
0
Order By: Relevance
“…Bolaform surfactants are also used in template synthesis for the production of micro-and meso-porous silica [314,315], and hydrophobic nanocalcium carbonate [316].…”
Section: Bolaform Surfactantsmentioning
confidence: 99%
“…Bolaform surfactants are also used in template synthesis for the production of micro-and meso-porous silica [314,315], and hydrophobic nanocalcium carbonate [316].…”
Section: Bolaform Surfactantsmentioning
confidence: 99%
“…Designed multihead quaternary ammonium surfactants like bolaform surfactants with different chain lengths and rigid benzene ring groups as structure-directing agents (SDAs), 3D cubic (Pm 3 ri) and face-centered cubic (Fd 3 m) mesoporous silicates were synthesized (19). Lately, the low symmetrical mesostructures with tetragonal and orthorhombic pores were also obtained (20). It has been clearly demonstrated that the derived mesostructures are remarkably influenced by the rational control of inorganic-organic interactions and cooperative assembly of the silica species and the surfactants.…”
Section: Introductionmentioning
confidence: 92%
“…Many procedures in which cationic surfactants were used as templates for the preparation of mesostructured silica materials have been reported. As the isoelectric point of silica lies at a pH value of B2, 42 silicon species in alkaline solutions are negatively charged which can be linked and stabilized by cationic surfactants (S + ) through strong electrostatic Coulomb forces in the S + I À pathway, leading to the formation of ordered mesostructured silica materials such as M41S, 36,37 FDU-2, 43 FDU-11 and FDU-13, 44 SBA-2, 45 SBA-6 46 and SBA-8, 47 etc. Likewise, cationic surfactants can also be used as templates to prepare silica mesostructures in strong acidic solutions (pH o 2) where the silicon species are positively charged.…”
Section: Synthesis Of Mesoporous Materialsmentioning
confidence: 99%